Activation of the PP2A catalytic subunit by ivabradine attenuates the development of diabetic cardiomyopathy. (May 2019) - Zuo, Guang-Feng; Ren, Xiao-Min; Ge, Qing; Luo, Jie; Ye, Peng; Wang, Feng; Wu, Wen; Chao, Yue-Lin; Gu, Yue; Gao, Xiao-Fei; Ge, Zhen; Gao, Han-Bin; et al.
Abstract: Hyperglycemia-induced apoptosis plays a critical role in the pathogenesis of diabetic cardiomyopathy (DCM). Our previous study demonstrated that ivabradine, a selective I f current antagonist, significantly attenuated myocardial apoptosis in diabetic mice, but the underlying mechanisms remained unknown. This study investigated the underlying mechanisms by which ivabradine exerts anti-apoptotic effects in experimental DCM. Pretreatment with ivabradine, but not ZD7288 (an established I f current blocker), profoundly inhibited high glucose-induced apoptosis via inactivation of nuclear factor (NF)-κB signaling in neonatal rat cardiomyocytes. The effect was abolished by transfection of an siRNA targeting protein phosphatase 2A catalytic subunit (PP2Ac). In streptozotocin-induced diabetic mice, ivabradine treatment significantly inhibited left ventricular hyperpolarization-activated cyclic nucleotide-gated channel 2 (HCN2) and HCN4 (major components of the I f current), activated PP2Ac, and attenuated NF-κB signaling activation and apoptosis, in line with improved histological abnormalities, fibrosis, and cardiac dysfunction without affecting hyperglycemia. These effects were not observed in diabetic mice with virus-mediated knockdown of HCN2 or HCN4 after myocardial injection, but were alleviated by knockdown of PP2Acα. Molecular docking and phosphatase activity assay confirmed direct binding of ivabradine to, and activation of, PP2Ac. In conclusion, ivabradine may directly activate PP2Ac, leading to inhibition of NF-κB signaling activation, myocardial apoptosis, and fibrosis, and eventually improving cardiac function in experimental DCM. Taken together, the present findings suggest that ivabradine may be a promising drug for treatment of DCM. Highlights: PP2Ac phosphorylation is important in hyperglycemia-induced cardiomyocyte apoptosis. Ivabradine, an I f current antagonist, binds and activates phosphorylated PP2Ac. Ivabradine exerts cardioprotective effects on diabetic cardiomyopathy via PP2Ac.